Vaccines for leishmaniasis and the implications of their development for American tegumentary leishmaniasis - Beatriz Coutinho De Oliveira; Malcolm S. Duthie; Valéria Rêgo Alves Pereira (Taylor & Francis Group, 2020)
The leishmaniases are a collection of vector-borne parasitic diseases caused by a number of different Leishmania species that are distributed worldwide. Clinical and laboratory research have together revealed several important immune components that control Leishmania infection and indicate the potential of immunization to prevent leishmaniasis. In this review we introduce previous and ongoing experimental research efforts to develop vaccines against Leishmania species. First, second and third generation vaccine strategies that have been proposed to counter cutaneous and visceral leishmaniasis (CL and VL, respectively) are summarized. One of the major bottlenecks in development is the transition from results in animal model studies to humans, and we highlight that although American tegumentary leishmaniasis (ATL; New World CL) can progress to destructive and disfiguring mucosal lesions, most research has been conducted using mouse models and Old World Leishmania species. We conclude that assessment of vaccine candidates in ATL settings therefore appears merited.